Molecular dynamics simulation of nanostructured materials an understanding of mechanical behavior - Pal, Snehanshu; Ray, Bankim Chandra (New York, NY : CRC Press, 2020)
Molecular dynamics simulation is a significant technique to gain insight into the mechanical behavior of nanostructured (NS) materials and associated underlying deformation mechanisms at the atomic scale. The purpose of this book is to detect and correlate critically current achievements and properly assess the state of the art in the mechanical behavior study of NS material in the perspective of the atomic scale simulation of the deformation process. More precisely, the book aims to provide representative examples of mechanical behavior studies carried out using molecular dynamics simulations, which provide contributory research findings toward progress in the field of NS material technology.
OCLC-licensed vendor bibliographic record.
Keywords: Nanostructured materials -- Mechanical properties; Molecular dynamics -- Simulation methods; MATHEMATICS / General; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Material Science